Analysis of sequence-defined oligomers through Advanced Polymer Chromatography™ – mass spectrometry hyphenation. Issue 58 (23rd September 2020) - Berg, Marie-Theres; Mertens, Chiel; Du Prez, Filip; Kühne, Thomas D.; Herberg, Artjom; Kuckling, Dirk
Abstract : The hyphenation of SEC and MS coupled with IMS allows for a quick and easy separation and identification of oligomers with different length and/or sequence. Abstract : In recent years, sequence-defined oligomers have attracted increasing interest in the polymer community and the number of new applications such as macromolecular data storage and encryption is increasing. However, techniques allowing sequence differentiation are still lacking. In this study, the focus is put towards a new strategy allowing structural distinction between sequence-defined oligomers with identical molecular weight and composition, but bearing different sequences. This technique relies on the hyphenation of size exclusion chromatography and mass spectrometry, coupled with ion mobility separation. This approach allows for a quick and easy separation and identification of oligomers with different length and/or sequence.